The potential role of clinical pharmacists in elderly patients during hospital admission - OKUYAN, BETÜL (GOVI-VERLAG PHARMAZEUTISCHER VERLAG GMBH, 2015)
The aim of this study was to show the potential impact of services directed by clinical pharmacists, including medication reconciliation and medication review, on the hospital admission process for elderly patients. This study was conducted in an internal medicine ward between April 24 and July 25, 2014. Patients hospitalized due to any reason were eligible if they were 65 years or older and regularly used at least one medication at home. The clinical pharmacist evaluated potentially inappropriate medications (PIM), medication related problems (MRPs) and medication discrepancies at the time when these eligible elderly patients were admitted to the hospital. The physician acceptance rate as related the clinical pharmacist's recommendation was evaluated retrospectively. A total of 133 elderly patients (mean age 76.62 8.12 years old; 70 female) were included in the study. Out of 394 medication discrepancies, 88.32% were found to be unintended discrepancies among 111 elderly patients upon hospital admission. PIM was found in 19.55% of these cases. A total of 396 MRPs among 115 patients were identified, with the most common being that the drug had not been taken/administered at all. The doctor acceptance rate of the clinical pharmacist's recommendation was found to be 85.60%. In conclusion, it was found that medication related problems and inappropriate medication utilization at admission could be prevented at a high rate of success by clinical pharmacist-driven medication reconciliation and medication review services.
Keywords: DRUG-RELATED PROBLEMS; MEDICATION RECONCILIATION; DISCREPANCIES; HISTORIES; MEDICINES; DISCHARGE; PROGRAM; COHORT; ERRORS; IMPACT